SPECIFICS OF TRADITIONAL FAIR TRADE OF KHARKIV IN THE XIX CENTURY (Південний архів (історичні науки), 2022)
All times society has always strived for economic stability through a material exchange. Society increased economic stability not only by the materials exchange, also a lot of attention paid to communication, transfer of experience, and exchange of spiritual values. Changes in industry and agriculture affected commercial and trading. The fair network provides circulation of the most important food and goods. In the 19th century, all economic activity of Dnieper Ukraine was closely relate to the Russian market. The fair industry was formed that times. Fairs had following types or specialization wholesale, periodical and held in some cities and towns. In the second half of the XIX century, fair trade was transformed. At first, the fairs were attended not only by ordinary traders, but also joint-stock companies and trading companies. Fairs was not only the trading platform, but also a place for loan and credit operations. In addition to large fairs, there were many cities and villages fairs. Traditionally fairs were scheduled on major Christian holidays. Traditions and trading history illustrate the principles of commercial behavior that show us dodge that still applicable during the economic crises, epidemics, and wars. Purpose. The main goal of this study is to highlight the typical features of trade and the specifics of fair trade in Kharkiv in the XIX century. Methods. The article is based mainly on comparative-typological and historical-cultural approaches, as well as on elements of the retrospective method of historical local lore. Results. The results of the investigation is in consideration of the peculiarities of the functioning of the Kharkiv fair trade and determine the specifics of the then trading system. Conclusions. Fairs trade has been and remains an important factor in attracting investment and boosting domestic and foreign trade. Nowadays, fairs trade is gaining new importance. It successfully combines trade, cultural, entertainment functions and preserves the traditional periodicity type.
Keywords: fair, commodity circulation, Kharkiv, merchant, product range.